2017
DOI: 10.1001/jama.2017.3421
|View full text |Cite
|
Sign up to set email alerts
|

Medical Journals, Publishers, and Conflict of Interest

Abstract: Publishers of scientific journals must be as invested as editors in defining and managing conflict of interest policies and practices, because the credibility and integrity of their publications constitute their most important asset. How and why a publisher engages in this effort are increasingly complex, given the exponential changes in biomedical journalism over the last 15 years. In addition, the world of medical journalism is affected by wider cultural trends in the media; in general, issues around conflic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…A brief remark on "publication bias" should be made regarding the current existing literature on the subject. 49,50 A thorough literature search was made, but only articles in English were reviewed. It was noticed that literature from export countries emphasized the negative components of medical tourism, whereas import countries focused mostly on its positive aspects.…”
Section: Resultsmentioning
confidence: 99%
“…A brief remark on "publication bias" should be made regarding the current existing literature on the subject. 49,50 A thorough literature search was made, but only articles in English were reviewed. It was noticed that literature from export countries emphasized the negative components of medical tourism, whereas import countries focused mostly on its positive aspects.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in my own institution, staff from the compliance office routinely examine Open Payments to verify voluntary disclosures by medical faculty (no purposeful omissions have been found thus far). Journal editors and peer reviewers will be able to use the database to verify the disclosures of authors of clinical trials 6 or guidelines. 7 For now the database contains information only on prescribers who practice in the United States, but global regulatory agencies have begun to take notice of our disclosure laws and are expected to follow suit.…”
Section: Verification Of Voluntary Financial Conflict Of Interest Dismentioning
confidence: 99%
“…Specifically, it has been suggested that journal-level financial relationships such as the acceptance of industry advertising revenue, reprint fees, and additional industry printing contracts held by journal parent companies may impact editorial decision-making, creating an environment more favourable to industry-sponsored research. [19][20][21] Editor COI and commercial publishing biases may be of particular concern given recent fears that non-peer-reviewed publications with aCOI are having significant impacts on biomedical research and clinical practice. 25 Certainly, available anecdotal evidence does suggest there may be cause for concern.…”
Section: Introductionmentioning
confidence: 99%
“…24 Furthermore, there are some data available indicating that commercial publishing biases may lead to editors being less diligent in the execution of journal aCOI policies for article authors. [19][20] As greater attention is paid to the potential adverse consequences of aCOI and industry funding on medical research, it is critical that ongoing discussions regarding commercial publishing biases occur in an evidence-rich environment.…”
Section: Introductionmentioning
confidence: 99%